2018
DOI: 10.1371/journal.pone.0197254
|View full text |Cite|
|
Sign up to set email alerts
|

ANKK1 is found in myogenic precursors and muscle fibers subtypes with glycolytic metabolism

Abstract: Ankyrin repeat and kinase domain containing 1 (ANKK1) gene has been widely related to neuropsychiatry disorders. The localization of ANKK1 in neural progenitors and its correlation with the cell cycle has suggested its participation in development. However, ANKK1 functions still need to be identified. Here, we have further characterized the ANKK1 localization in vivo and in vitro, by using immunolabeling, quantitative real-time PCR and Western blot in the myogenic lineage. Histologic investigations in mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…We also found that ANKK1 has an impact on the cell cycle that is affected by ANKK1 polymorphisms and APO treatment [18]. Additionally, the expression of ANKK1 is not restricted to the CNS, but extends to the myogenic lineage [109]. We observed ANKK1 in migrating myoblasts and satellite cells, which are muscle precursors.…”
Section: Ankk1 Protein Brain Structure and Addictionsupporting
confidence: 51%
See 1 more Smart Citation
“…We also found that ANKK1 has an impact on the cell cycle that is affected by ANKK1 polymorphisms and APO treatment [18]. Additionally, the expression of ANKK1 is not restricted to the CNS, but extends to the myogenic lineage [109]. We observed ANKK1 in migrating myoblasts and satellite cells, which are muscle precursors.…”
Section: Ankk1 Protein Brain Structure and Addictionsupporting
confidence: 51%
“…ANKK1, also known as RIP5, belongs to the RIP serine-threonine kinase family, which regulates and induces both intracellular inflammatory signaling pathways or, apoptotic or necrotic cell death [112,113]. The RIP family participates in the differentiation of a broad variety of cell types and tissues [114]: RIP2 and ANKK1 in myogenic differentiation [109,115], RIP4 (homologous to ANKK1 at both the N-terminal kinase domain and the C-terminal ankyrin repeats) in epidermal morphogenesis during development and cutaneous wound repair [116] and, RIP7 and ANKK1 in neuronal differentiation [17,18,117]. Altogether, these data are in agreement for a relevant role of ANKK1 during development.…”
Section: Ankk1 Protein Brain Structure and Addictionmentioning
confidence: 99%
“…ANKK1 ( ankyrin repeat and kinase domain containing 1 ; Gene ID: 255239) encodes for a protein that belongs to the Ser/Thr protein kinase family and to the protein kinase superfamily that is involved in signal transduction pathways. Its relation with neuropsychiatric disorders, its localization in neural progenitors and its correlation with the cell cycle, suggested that ANKK1 could participate in neural development [ 138 ] and in the regulation of the metabolism of muscles during development and in adulthood [ 139 ]. Even CSDC2 ( cold shock domain-containing C2 ; Gene ID: 27254) that encodes for an RNA-binding protein is involved in the myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The underexpression of CXCL3 suggests an inference of male cell differentiative potency, as well as those of ANKK1 , CAMTA1 and CSDC2 involved in different stem cell commitment. In fact, in the last decade, chemokines have been implicated in cell differentiation [ 145 , 146 ] and CXCL3 positively regulates adipogenic differentiation in mouse preadipocyte and MSC cell lines [ 139 ]. This evidence together with TRAM results on CXCL3 underexpression suggests that human male derived ADSCs could be less prone to differentiate toward the adipogenic fate than the female counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Negative results from the SGP xpo-1 RNAi could be attributed to protein stability of XPO-1 and its inheritance from previous cell divisions. To circumvent the persistence of inherited XPO-1, we treated worms with Leptomycin B (LMB, 2ng/mL (Perander et al, 2001;Rubio-Solsona et al, 2018)) to block XPO-1 function. Synchronized L1 worms were grown in liquid culture containing either OP50 bacteria or OP50 supplemented with LMB and DTCs were quantified at the late L3 stage.…”
Section: Xpo-1 Asymmetrically Regulates the Nuclear Level Of Sys-1mentioning
confidence: 99%